2019
DOI: 10.2196/11957
|View full text |Cite
|
Sign up to set email alerts
|

Needs Analysis for a Parenting App to Prevent Unintentional Injury in Newborn Babies and Toddlers: Focus Group and Survey Study Among Chinese Caregivers

Abstract: Background With the growing popularity of mobile health technology, app-based interventions delivered by smartphone have become an increasingly important strategy toward injury prevention. Objective This study aimed to develop a framework supporting the design of an app-based intervention to prevent unintentional injury, targeted for caregivers of Chinese children aged 0 to 6 years. Methods A theory-based mixed-method study, including focus g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
10
0
2
Order By: Relevance
“…With regard to the study by Jabaley et al [49], using an iPhone (mobile device) as an in-home child safety intervention among 3 families with young children reduced home hazards to almost zero [46]. Similar studies on injury prevention apps for parents and caregivers have also been undertaken by Roberts et al [17], McKenzie et al [11], Chow et al [21], and Ning et al [18][19][20], and these indicated that such apps have improved parental safety knowledge, environmental modification, and successfully facilitated behavior change.…”
Section: Using Cfir and Diffusion Of Innovation Theory (Proposed Bymentioning
confidence: 90%
See 1 more Smart Citation
“…With regard to the study by Jabaley et al [49], using an iPhone (mobile device) as an in-home child safety intervention among 3 families with young children reduced home hazards to almost zero [46]. Similar studies on injury prevention apps for parents and caregivers have also been undertaken by Roberts et al [17], McKenzie et al [11], Chow et al [21], and Ning et al [18][19][20], and these indicated that such apps have improved parental safety knowledge, environmental modification, and successfully facilitated behavior change.…”
Section: Using Cfir and Diffusion Of Innovation Theory (Proposed Bymentioning
confidence: 90%
“…Smartphones are predominantly seen as a promising and cost-effective medium to deliver health-related interventions [ 16 ]. To date, there are a few app-based interventions developed for unintentional home injuries; for example, Make Safe Happen for parents of children aged 0-12 years [ 11 , 17 ], Caregivers for children aged 0-6 years [ 18 ], Primary Caregivers of preschoolers aged 3-6 years [ 19 , 20 ], and Mothers with children under 3 years of age [ 21 ]. Education and promotion can be implemented through this platform to reach a larger segment of the population.…”
Section: Introductionmentioning
confidence: 99%
“…Among the components that receive focus are usability of the device and app, capacities of the learners, and social interaction between users. We followed the FRAME model when developing the app and its multiple components; we implemented the FRAME model through results from a needs assessment that consisted of a series of focus groups plus online surveys among key stakeholders, including preschool teachers and caregivers of preschoolers [23].…”
Section: Methodsmentioning
confidence: 99%
“…A literatura científica demonstra que os aplicativos móveis, juntamente com as informações que eles proporcionam, podem ser empregados para melhorar os resultados de saúde e reduzir os riscos, principalmente em programas educacionais. Eles também desempenham um papel importante na compreensão dos fatores que afetam a saúde dos recémnascidos 16 .…”
Section: Introductionunclassified